Effect of Bisoprolol on the Level of Dabigatran. (March 2020) - Nehaj, Frantisek; Sokol, Juraj; Ivankova, Jela; Mokan, Michal; Mokan, Marian
Abstract : Background: Many patients receiving dabigatran treatment might also require bisoprolol therapy. However, there is a possibility that bisoprolol as significant P-glycoprotein inhibitor might interact with dabigatran. Study Question: To investigate the impact of concomitant bisoprolol therapy on dabigatran plasma level in patients with nonvalvular atrial fibrillation. Study Design: A pilot drug interaction study in 29 patients with nonvalvular atrial fibrillation on dabigatran therapy. Bisoprolol was administrated in 18 patients. Blood samples were collected at baseline (in the morning, before any medication was administered) and at hour 2 (2 hours after administration of dabigatran and bisoprolol). Results: The dabigatran plasma level was significantly higher at baseline and at hour 2 in patients treated with bisoprolol compared with patients without bisoprolol therapy. In addition, we have shown that this increase is affected by dabigatran dosage and concomitant treatment with proton-pump inhibitor and digoxin. The impact of bisoprolol on dabigatran concentration was still significant despite these confounders. Conclusions: This study demonstrated the interaction between dabigatran and bisoprolol, which is modulated with dabigatran dosage and concomitant treatment with proton-pump inhibitor and digoxin.